Catalytic Double Cyclization Process for Antitumor Agents against Breast Cancer Cell Lines - Mancuso, Raffaella; Ziccarelli, Ida; Chimento, Adele; Marino, Nadia; Della Ca’, Nicola; Sirianni, Rosa; Pezzi, Vincenzo; Gabriele, Bartolo (iScience, 2018)
The development of efficient synthetic strategies for the discovery of novel antitumor molecules is a major goal in current research. In this context, we report here a catalytic double cyclization process leading to bicyclic heterocycles with significant antitumor activity on different human breast cancer (BC) cell lines. The products, 6,6a-dihydrofuro[3,2-b]furan-2(5H)-ones, were obtained in one step, starting from simple substrates (4-yne-1,3-diols, CO, and O2), under the catalytic action of PdI2 in conjunction with KI. These compounds have significant antiproliferative activity in vitro on human BC cell lines, both hormone receptor positive (MCF-7) and triple negative (triple-negative breast cancer [TNBC]; MDA-MB-231 and MDAMB-468), while exhibiting practically no effects on normal MCF-10A (human mammary epithelial) and 3T3-L1 (murine fibroblasts) cells. Thus, these compounds have the potential to expand the therapeutic options against BC, and in particular, against its most aggressive forms (TNBCs). Moreover, the present synthetic approach may provide an economic benefit for their production. [Display omitted] •Novel catalytic double cyclization method leading to bicyclic heterocycles in one step•Direct synthesis of antitumor agents from simple substrates (4-yne-1,3-diols and CO)•Identification of a new class of antitumor agents against breast cancer (BC) cells•Significant antitumor activity against the most aggressive triple-negative BC cells Drugs; Organic Synthesis; Toxicology Evaluation